A 40 Gbps optical transceiver for particle physics experiments. (1st May 2022) - Deng, B.; Huang, X.; Sun, H.; Chao, C.-P.; Chen, S.-W.; Gong, D.; Hou, S.; Huang, G.; Li, C.-Y.; Liu, C.; Liu, T.; Sun, Q.; et al.
Abstract: We present the design and the test results of a quad-channel optical transceiver module (QTRx) possibly for future particle physics experiments. The transmitters of QTRx, each at 10 Gbps, are based on a Quad-channel VCSEL Diode array Driver (QLDD) and 1 × 4 VCSEL array. The receivers of QTRx, with data rates of 2.56 Gbps or 10 Gbps per channel, are based on a Quad-channel Trans-Impedance and limiting Amplifier (QTIA) and 1 × 4 photodiode array of GaAs or InGaAs. QTRx is 20 mm × 10 mm × 5 mm and couples to an MT fiber connector. Test results indicate that QTRx achieves the design goals with a power consumption of 124 mW per transmitter channel at 10 Gbps and 120 mW at 2.56 Gbps per receiver channel with an on-chip charge pump. The sensitivities of QTIA are −17 dBm at 2.56 Gbps and −8 dBm at 10 Gbps, respectively. Further improvements with a gold-finger interface and a more compact optical lens are being designed.